A novel LiSnVO4 anode material for lithium-ion batteries - Teo, L.P.; Buraidah, M.H.; Arof, Abdul Kariem (Springer Verlag (Germany), 2015)
In this work, a new material LiSnVO4 has been prepared via sol-gel method utilizing ammonium metavanadate, acetates of tin and lithium as starting materials, and nitric acid and oxalic acid as complexing agents. The amount of starting materials used has been chosen so that the mole ratio of Li/Sn/V is 1:1:1. The sol-gel precursor has been sintered at 700 °C for 6 h. Based on thermogravimetry analysis (TGA) analysis, the formation mechanism suggested the product to be LiSnVO4. Energy-dispersive X-ray analysis (EDX) reveals the ~1:1 ratio of Sn:V. EDX results agree reasonably with the formation mechanism from TGA analysis that the Sn:V ratio is 1:1. Results from X-ray photoelectron spectroscopy (XPS) indicate that the oxidation states of Li, Sn, and V are +1, +2, and +5, respectively. Since there is no ICDD data available to match the XRD diffractogram of the material obtained, CMPR and powder diffraction data interpretation and indexing program (POWD) softwares have been used to predict the crystal structure system to be tetragonal (similar to that of SnO2). A fabricated LiSnVO4//Li cell can deliver a large initial irreversible discharge capacity of 1270 mAh g−1 and reversible capacity of 305.4 mAh g−1 at the end of second cycle, which drops to 211 mAh g−1 at the end of 53rd cycle. The capacity retention is 69 % with respect to the second discharge capacity.